MODEL OF ORGANIZATION OF PHYSICAL AND HEALTH ACTIVITY OF EMPLOYEES OF REMOTE INDUSTRIAL FACILITIES BY MEANS OF INFORMATION TECHNOLOGIES - Moiseenko, A.V.; Dmitriev, V.A.; Karpova, I.A.; Kapilevich, L.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a model for organizing physical culture and health-improving activities of workers at remote industrial facilities based on information technology and evaluate its effectiveness. Methods and structure of the study. Scientific work was carried out on the basis of enterprises of the oil and gas complex located in the northern regions of the Siberian Federal District. In total, 500 people working on a rotational basis were examined - men aged 25 to 50 years. Questionnaire and testing methods were used (calculation of biological age, Rufier's test, Stange's test, Harvard step test). Results and conclusions. The developed model includes three blocks - diagnostic, organizational and activity and control. For each block, the main content is formulated, the implementation technologies and the results that will be obtained in this block are determined. The result is a personalized training program. In the course of its implementation, an automated control over the state of students is carried out according to the criteria presented in the control block of the model.